2017
DOI: 10.1016/j.geoderma.2016.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and improvement of the default soil hydraulic parameters for the Noah Land Surface Model

Abstract: Soil hydraulic parameters used in estimating soil water and energy fluxes are included in a lookup table in the Noah Land Surface Model (LSM). The purpose of the study was to examine the Noah default soil hydraulic parameters and compare them to soil measurements across Texas, USA. These default soil parameters were compared to measured soil properties from a soil database including 6,749 soil samples located within and around Texas. Mean differences between measured and default soil parameters were tested usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 43 publications
3
52
0
Order By: Relevance
“…It is also important to note that future phases of NLDAS and the NCEP Unified Land Data Assimilation System (NULDAS) will contain operational data assimilation of soil moisture and snow. Problems with NLDAS model soil hydraulic parameters and model structure should be addressed, given that improved parameterizations result in more realistic soil moisture dynamics (Kishné et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note that future phases of NLDAS and the NCEP Unified Land Data Assimilation System (NULDAS) will contain operational data assimilation of soil moisture and snow. Problems with NLDAS model soil hydraulic parameters and model structure should be addressed, given that improved parameterizations result in more realistic soil moisture dynamics (Kishné et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Most LSMs mainly use default soil parameters, oversimplifying their influence. Kishné et al () found that using measured and PTF‐estimated water content at field capacity and wilting point yielded a 35 to 76% decrease in plant available water compared to default model settings.…”
Section: Ptfs In Earth System Sciencesmentioning
confidence: 99%
“…The hydraulic conductivity is largely nonlinear relying on the SM with sensitivity to SM fluctuations and soil properties (Cuenca et al, 1996). Yet the hydraulic conductivity associated with other soil variables is default defined in the Noah LSM as constants according to the soil texture map (Chen & Dudhia, 2001;Cosby et al, 1984;Ek et al, 2003), which indeed cannot provide optimal soil hydraulic properties (Kishné et al, 2017;Shellito et al, 2016). Besides, reasonable vertical soil hydrology in Noah model is also hampered by the layer soil texture used to represent the entire 2-m soil column (Xia et al, 2015).…”
Section: 1029/2018wr024326mentioning
confidence: 99%